Energy Poverty (Dis)Assembling Europe's Infrastructural Divide - Bouzarovski, Stefan (Springer International Publishing, 2018)
This open access book aims to consolidate and advance debates on European and global energy poverty by exploring the political and infrastructural drivers and implications of the condition across a variety of spatial scales. It highlights the need for a geographical conceptualization of the different ways in which household-level energy deprivation both influences and is contingent upon disparities occurring at a wider range of spatial scales. There is a strong focus on the relationships among energy transformation, institutional change and place-based factors in determining the nature and location of energy-related injustices. The book also explores how patterns and structures of energy poverty have changed over time, as evidenced by some of the common measures used to describe the condition. In part, this means investigating the makeup of energy poor demographics across various social and spatial cleavages. More broadly, it also argues that energy sector reconfigurations are both reflected in and shaped by various domains of social and political organization, especially in terms of creating poverty-relevant outcomes.